2012
DOI: 10.1155/2012/564027
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of CD34+CXCR4+ Stem/Progenitor Cells and the Parameters of Left Ventricular Function and Remodeling in 1-Year Follow-up of Patients with Acute Myocardial Infarction

Abstract: Mobilization of stem cells in acute MI might signify the reparatory response. Aim of the Study. Prospective evaluation of correlation between CD34+CXCR4+ cell mobilization and improvement of LVEF and remodeling in patients with acute MI in 1-year followup. Methods. 50 patients with MI, 28 with stable angina (SAP), and 20 individuals with no CAD (CTRL). CD34+CXCR4+ cells, SDF-1, G-CSF, troponin I (TnI) and NT-proBNP were measured on admission and 1 year after MI. Echocardiography and ergospirometry were carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
4
29
1
Order By: Relevance
“…21-23 A previous study of AMI patients demonstrated that the number of CD34 + CXCR4 + cells mobilized into the peripheral blood after AMI was significantly higher in patients with improved LV function and attenuated LV remodeling at the 1-year follow-up compared with patients without functional improvement. 18 Another study of AMI patients reported that the number of mobilized EPCs in the peripheral blood and the potential of those EPCs to differentiate into endothelial cells correlated with greater myocardial salvage, decreased end-systolic volume, and increased EF recovery 6 months after AMI. 24 Based on these reports, the main contribution of CD34 + cells and EPCs to AMI is considered neovascularization.…”
Section: Remodeling and Muse Cell Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…21-23 A previous study of AMI patients demonstrated that the number of CD34 + CXCR4 + cells mobilized into the peripheral blood after AMI was significantly higher in patients with improved LV function and attenuated LV remodeling at the 1-year follow-up compared with patients without functional improvement. 18 Another study of AMI patients reported that the number of mobilized EPCs in the peripheral blood and the potential of those EPCs to differentiate into endothelial cells correlated with greater myocardial salvage, decreased end-systolic volume, and increased EF recovery 6 months after AMI. 24 Based on these reports, the main contribution of CD34 + cells and EPCs to AMI is considered neovascularization.…”
Section: Remodeling and Muse Cell Numbermentioning
confidence: 99%
“…24 Based on these reports, the main contribution of CD34 + cells and EPCs to AMI is considered neovascularization. [17][18][19] In animal models other than AMI, Muse cells have been shown to home into damaged tissue and differentiate spontaneously into cells compatible with the tissue they targeted and repair damaged tissue. 1,7-10 If the same mechanism is applied, it is suggested they repair AMI tissue more directly through replenishing new cardiomyocytes, and in fact, we have reported this in a rabbit model of AMI.…”
Section: Remodeling and Muse Cell Numbermentioning
confidence: 99%
“…The mobilization of BM-derived stem cells (BM-SCs) in patients with acute MI is considered a reparatory response, [21][22][23][24] and experimental studies have suggested an important role of BMSCs in cardiac repair response after MI. 13,20,[24][25][26][27][28][29] Nevertheless, the contribution of circulating cells to myocardial and endothelial repair is still incompletely understood. Moreover, the mobilization of endothelial progenitor cells correlates with the ischemic zone and not with the necrotic zone of patients after MI, 30 suggesting the possibility of an active mechanism originating from the ischemic border zone of the heart that is transmitted to the BM.…”
Section: Mobilization and Homing Of Bm Progenitor Cellsmentioning
confidence: 99%
“…Four studies were conducted on a total of n=309 patients with acute myocardial infarction, overall showing that high CD34 + /CD133 + CPCs predicted improvements in regional or global left ventricular function, [37][38][39] and in coronary flow reserve. 40 One study found that mobilization of EPCs during acute ischemia was significantly lower in patients who developed restenosis, 41 whereas a small study in patients with stable angina showed that EPC levels directly correlated with the degree of restenosis.…”
Section: Excluded Studiesmentioning
confidence: 99%